Making Marks : Architects' Sketchbooks - The Creative Process. - Jones, Will (London : Thames & Hudson, 2019)
Adams, Ben ; Aires Mateus, Manuel ; Arets, Wil ; Balmond, Cecil ; van Berkel, Ben ; Berton, Peter ; Brillhart, Jacob ; Campo Baez, Alberto ; Coenen, Jo ; Diamond, Jack ; Dubbeldam, Heather ; France-Lanord, Albert ; Fuksas, Massimiliano ; Garcia Saxe, Benjamin ; Gebler, Sasha ; Graham, Meg ; Hølmebakk, Carl-Viggo ; Igarashi, Jun ; Inge, Anderson ; von Klemperer, James ; Kuwabara, Bruce ; Lee, Christopher ; Leth, Uffe ; Libeskind, Daniel ; MacKay-Lyons, Brian ; Macullo, Davide ; Mariani, Massimo ; McLaughlin, Tara ; Miners, Rob ; Morris, Peter ; Netkin, Brad ; O'Looney, Benedict ; di Pasquale, Joseph ; Pich-Aguilera, Felipe ; Podwojewski, Pawel ; Puri, Sanjay ; la Roi, Matthijs ; Safdie, Moshe ; Saunt, Deborah ; Soules, Jon ; de Vries, Nijs ; Whittle, Kristen
boek